2020
DOI: 10.12659/ajcr.921123
|View full text |Cite
|
Sign up to set email alerts
|

Safe and Effective Use of Bilateral Erector Spinae Block in Patient Suffering from Post-operative Coagulopathy following Hepatectomy

Abstract: Unusual clinical course Background:Regional nerve blocks ideally provide safe and effective post-operative pain control, decrease opiate requirements, and enhance recovery from intense pain following major thoracic, abdominal, and musculoskeletal surgeries. The erector spinae plane block, a recently described novel treatment for chronic neuropathic pain and acute pain after thoracic surgery, can be performed with in plane infiltration and placement of a continuous infusion catheter deep to the erector spinae m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
18
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 15 publications
0
18
0
1
Order By: Relevance
“…Maddineni et al 17 reported a successful outcome of ESP as a replacement for gold standard epidural analgesia in achieving effective pain control following hepatic surgery. Similarly, a study by Gürkan 18 has shown that US-guided ESP block and PVB provided adequate analgesia in patients undergoing breast surgery and have an opioid sparing effect by reducing morphine consumption.…”
Section: Discussionmentioning
confidence: 99%
“…Maddineni et al 17 reported a successful outcome of ESP as a replacement for gold standard epidural analgesia in achieving effective pain control following hepatic surgery. Similarly, a study by Gürkan 18 has shown that US-guided ESP block and PVB provided adequate analgesia in patients undergoing breast surgery and have an opioid sparing effect by reducing morphine consumption.…”
Section: Discussionmentioning
confidence: 99%
“…This has been described in two studies, which narrate that the ESPB is a safer option in the presence of systemic anticoagulation, use of antiplatelet medications, coagulation disorders, and following heparinization, which are contraindications to TEA [ 19 , 20 ]. Maddineni et al also described the novel use of the ESPB for analgesia and safe catheter removal in the setting of anticoagulation undergoing major hepatic surgery for intrahepatic cholangiocarcinoma [ 21 ]. Therefore, ESPB seems much safer than TEA after donor hepatectomy in the presence of decreased platelets and increased INR.…”
Section: Discussionmentioning
confidence: 99%
“…We introduced the catheters preoperatively to reduce the stress response during surgery. We found that the patient remained hemodynamically stable in contrast to a continuous epidural infusion in which frequent episodes of hypotension are often encountered [ 3 , 4 ]. He did not require additional doses of fentanyl intraoperatively after the initial dose at induction.…”
mentioning
confidence: 99%
“…The use of bilateral continuous block ensured ongoing pain relief [ 2 ]. There is a lack of consensus on the type, dose, and concentration of local anesthetic for this block [ 3 ]. We used ropivacaine 0.2% with fentanyl 2 μg/ml at the rate of 7 ml/h, which provided adequate analgesia.…”
mentioning
confidence: 99%
See 1 more Smart Citation